(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2017)
Background: The world comprises of 1.2 billion of Adolescents. India has the largest population of adolescents in the world being home to 243 million individuals aged between 10-19 years that hold the future powerhouse of the country. During this phase adolescents go through a lot of changes. Peer Pressure is very high during adolescence; following the trend makes them eat non-nutritious junk food which leads to lifestyle disorders. A finger food like Tea cake will be a fancy option for adolescents as a snack which will take care of calcium need, as this nutrient is essential for adolescent period. Objective: The purpose of the study was to develop a Calcium rich Vegan chocolate tea cake for Adolescents and perform Sensory evaluation for the developed product. Methodology: The recipe developed was Vegan, with chocolate flavor from unsweetened cocoa powder, as it’s the most popular flavor among adolescents and has array of health benefits. Five variations of Chocolate Tea Cakes were developed having different proportion of Refined Flour, Ragi Flour and Whole Wheat Flour into it. Sensory evaluation was done by 40 semi-trained adolescents. Results: The findings showed that the Tea Cake developed by combination of Ragi and Whole Wheat Flour was more acceptable than the one developed by only Refined Flour. The sample with Ragi and Whole Wheat flour was not just tasty but met other sensory parameters too, only the colour of the cake was a few shade darker than the other samples. Conclusion: The study revealed that popular snacks can easily be converted into healthy substitutes. The sample Tea cake which was substituted with 100% Ragi and Whole Wheat Flour mixture was the most acceptable sample of all.